Rational Design of Non-precious Metal Oxide Catalysts by Means of Advanced Synthetic and Promotional Routes - Konsolakis, Michalis; Stathopoulos, Vassilis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprinted edition of the Special Issue entitled "Rational Design of Non-Precious Metal Oxide Catalysts by Means of Advanced Synthetic and Promotional Routes" covers some of the recent advances in relation to the fabrication and fine-tuning of metal oxide catalysts by means of advanced synthetic and/or promotional routes. It consists of fourteen high-quality papers on various aspects of catalysis, related to the rational design and fine-tuning strategies during some of the most relevant applications in heterogeneous catalysis, such as N2O decomposition, the dry reforming of methane (DRM), methane combustion and partial oxidation, and selective catalytic reduction (SCR), among others.